RELATIONSHIP BETWEEN PREDISPOSING FACTORS AND UNMET NEED FOR FAMILY PLANNING CONTRACEPTION, WEST SUMATRA PROVINCE - Lia Nurdini (HUMAN CARE JOURNAL, 2021)
Unmet need for contraception is an inconsistency of contraceptive requirement. This study aims to determine the relationship between predisposing factors and the unmet needs of type 1 and the unmet needs of type 2 family planning in West Sumatra Province. This was a study using data from National Mid-Term Development Plan Survey (SRPJMN) of West Sumatra, with a total sample of 1180 couples of reproductive age. The categories of dependent variable were type 1 unmet need, type 2 unmet need, and met need. Independent variables consists of predisposing. The results showed that the majority (58.5%) of the subjects were> 35 years old, with ≤2 (57.7%) children and living in rural areas (60.9%). The level of unmet need for type 2 (29.7%) was much higher than that of type 1 unmet need (22.2%). The results of the multivariate analysis showed that the variables associated with type 1 unmet need were education (p = 0.028) and residence (p = 0.025). In unmet need type 2 the related variable is residence (p = 0.012). Recommendations are addressed to family planning health workers in order to improve quality in family planning services, collaborate with religious leaders and community leaders to commit effective counseling so it can improve the needs of contraception and rational use of family planning.Keywords: type 1 unmet need, type 2 unmet need, family planning